Land Law Evolution and Investment Dynamics: Historical Perspective and Contemporary Development Nexus - B. F. Sihombing; Farhan Hamid (APPTHI, 2023)
Abstract. The enactment of Indonesia’s Job Creation Law in 2020, known as the Omnibus Law, marked a pivotal moment in the country’s pursuit of economic growth and legal reform, aiming to foster job opportunities and sustainable development while streamlining regulatory frameworks and attracting investments. This paper presents a comprehensive analysis that explores the law’s implications in comparison with historical policies such as the 1992 Deregulation Policy Package and the 1993 Deregulation Policy Package. Utilizing qualitative methodology, the research investigates economic impacts through a thorough review of legal documents, policy reports, scholarly articles, and relevant literature, employing thematic analysis to uncover recurrent themes and patterns. The study elucidates how these policies have shaped Indonesia’s economic landscape, highlighting their interplay and contribution to the nation’s ongoing economic trajectory, offering valuable insights into the intricate dynamics between legal reforms and economic development. Abstrak. Pemberlakuan Undang-Undang Cipta Kerja di Indonesia pada tahun 2020, yang dikenal sebagai Omnibus Law, menandai momen penting dalam upaya pertumbuhan ekonomi dan reformasi hukum negara tersebut, dengan tujuan menciptakan peluang kerja dan pembangunan berkelanjutan sambil menyederhanakan kerangka regulasi dan menarik investasi. Makalah ini menyajikan analisis komprehensif yang menjelajahi implikasi hukum ini dibandingkan dengan kebijakan historis seperti Paket Kebijakan Deregulasi 1992 dan Paket Kebijakan Deregulasi 1993. Dengan menggunakan metodologi kualitatif, penelitian ini menyelidiki dampak ekonomi melalui tinjauan mendalam terhadap dokumen hukum, laporan kebijakan, artikel ilmiah, dan literatur relevan, dengan menerapkan analisis tematik untuk mengungkapkan tema-tema dan pola-pola yang berulang. Studi ini menjelaskan bagaimana kebijakan-kebijakan ini telah membentuk lanskap ekonomi Indonesia, menyoroti interplay mereka dan kontribusi terhadap lintasan ekonomi negara, memberikan wawasan berharga tentang dinamika rumit antara reformasi hukum dan pembangunan ekonomi. Kata kunci: Undang-Undang Cipta Kerja, Dampak ekonomi, Reformasi hukum, Pembangunan berkelanjutan, Daya tarik investasi